2017
DOI: 10.1101/132258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA regulation of the MRN complex impacts DNA damage, cellular senescence and angiogenic signaling

Abstract: MicroRNAs contribute to biological robustness by buffering cellular processes from external perturbations. Here we report an unexpected link between DNA damage response and angiogenic signaling that is buffered by two distinct microRNAs. We demonstrate that genotoxic stress-induced miR-494 and miR-99b inhibit the DNA repair machinery by targeting the MRE11a-RAD50-NBN (MRN) complex. Functionally, gain and loss of function experiments show that miR-494 and miR-99b affect telomerase activity, activate p21 and Rb … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…We previously showed that miR-494 is responsive to radiation and chemical inducers of genotoxic stress and functions to increase endothelial senescence during DNA damage responses (24). Given the intricate relationship between radiation, oxidative stress and ER stress (14,17), we asked if ER stress affected miR-494 expression and function.…”
Section: Er Stress Induces Mir-494 In Vitromentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that miR-494 is responsive to radiation and chemical inducers of genotoxic stress and functions to increase endothelial senescence during DNA damage responses (24). Given the intricate relationship between radiation, oxidative stress and ER stress (14,17), we asked if ER stress affected miR-494 expression and function.…”
Section: Er Stress Induces Mir-494 In Vitromentioning
confidence: 99%
“…miRs typically are thought to regulate numerous targets in a context dependent manner. We have previously shown that miR-494 targets the Mre11a, Rad50, Nbn (MRN) complex in the DNA damage repair pathway in response to genotoxic stressors (24). To identify the targets relevant for miR-494 in the context of ER stress, we undertook a proteomics-based approach.…”
Section: Mass Spectrometry Identifies Putative Targets Of Mir-494 Relmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on how severe the damage is, endothelial cells (ECs) make quick decisions among cell death, cell cycle arrest or survival. We have demonstrated how the expression of specific group of miRs can influence endothelial fate [1,2] in the context of DNA damage responses. However, the role of long non-coding RNAs (lncRNAs) in the endothelial stress responses is unclear.…”
mentioning
confidence: 99%